Electrolyte additive composition, electrolyte and battery
By using the electrolyte additive composition of lithium salt additive and electrolyte functional additive in lithium-ion batteries, the problem of capacity decay at high voltage is solved. By forming a protective film and eliminating harmful substances, the cycle life of the battery is extended and the stability of the electrolyte is improved.
Patent Information
- Application Number
- CN202412000175.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The capacity of lithium-ion batteries is severely decayed during the cycle under high voltage, mainly due to the oxidation and decomposition of the solvent and lithium salt in the electrolyte on the surface of the positive electrode, resulting in the structural damage of the positive electrode material and the dissolution of the transition metal.
An electrolyte additive composition is adopted, including lithium salt additives and electrolyte functional additives. The electrolyte functional additive has a specific structural formula, which can form a uniform and dense protective film on the surface of the positive electrode, inhibit the oxidative decomposition of the electrolyte, and eliminate harmful substances such as water and HF through N-Si bonds.
By forming a stable protective film and eliminating harmful substances, the internal resistance of the battery is significantly reduced, the side reactions on the positive electrode surface and the dissolution of transition metals are reduced, the cycle life of the battery is extended, and the chemical stability of the electrolyte is improved.
Smart Images

Figure CN119786735A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to an electrolyte additive composition, an electrolyte and a battery. Background Art
[0002] With the development of portable electronic devices and electric vehicles, consumers have increasing requirements for battery life. The energy density of the battery directly determines the duration of a single use, and high energy density can provide longer use time. At present, the energy density is mostly increased by increasing the working voltage of lithium-ion batteries. However, with the continuous increase in the working voltage, the electrode potential of the positive electrode material increases accordingly, which will bring a series of negative effects, mainly reflected in: under high voltage, the solvent molecules and lithium salts in the electrolyte are more likely to be oxidized and decomposed on the positive electrode surface, generating harmful substances such as water and HF, which will not only consume active lithium, but also react with the positive electrode material, resulting in structural damage to the positive electrode material and dissolution of transition metals. After the transition metal is dissolved, it may be reduced on the negative electrode surface, destroying the solid electrolyte interface film (ie, SEI film) on the negative electrode surface, further exacerbating the increase in the internal resistance of the battery, resulting in serious capacity decay of the battery during the cycle. Summary of the invention
[0003] The main purpose of the present application is to provide an electrolyte additive composition, an electrolyte and a battery to solve the problem of capacity attenuation of the battery during cycling at high voltage in the related art.
[0004] In order to achieve the above-mentioned object, according to the first aspect of the present application, an electrolyte additive composition is provided, the electrolyte additive composition comprising a lithium salt additive and an electrolyte functional additive, the structural formula of the electrolyte functional additive is shown in Formula 1:
[0005]
[0006] Furthermore, the mass ratio of the lithium salt additive to the electrolyte functional additive is (0.5-1):(0.3-1).
[0007] Furthermore, the electrolyte additive composition also includes a carbonate additive; the mass ratio of the carbonate additive to the electrolyte functional additive is (0-1): (0.3-1).
[0008] Furthermore, the carbonate additive includes at least one of vinylene carbonate and fluoroethylene carbonate.
[0009] Furthermore, the lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium borate, lithium difluoroborate, and lithium hexafluorophosphate.
[0010] Furthermore, the electrolyte additive composition also includes a sulfur-containing additive; the mass ratio of the sulfur-containing additive to the electrolyte functional additive is (0.5-3): (0.3-1).
[0011] Furthermore, the sulfur-containing additive includes at least one of propylene sulfite, 1,3-propane sultone, and ethylene sulfate.
[0012] According to a third aspect of the present application, an electrolyte is provided, the electrolyte comprising a lithium salt, an organic solvent and the electrolyte additive composition provided in the second aspect.
[0013] Further, the mass fraction of lithium salt in the electrolyte is 10% to 15%; and / or,
[0014] The mass fraction of the organic solvent in the electrolyte is 80% to 90%; and / or,
[0015] The mass fraction of the electrolyte additive composition in the electrolyte is greater than 0 and less than or equal to 5%.
[0016] Furthermore, the mass fraction of the electrolyte functional additive in the electrolyte is 0.3% to 1%; and / or,
[0017] The mass fraction of the lithium salt additive in the electrolyte is 0.5% to 1%; and / or,
[0018] The mass fraction of carbonate additives in the electrolyte is 0-1%; and / or,
[0019] The mass fraction of the sulfur-containing additive in the electrolyte is 0.5% to 3%.
[0020] Furthermore, the organic solvent includes at least one of cyclic carbonate, chain carbonate, and chain carboxylic acid ester.
[0021] Furthermore, the organic solvent includes cyclic carbonate, chain carbonate and chain carboxylic acid ester, wherein the mass ratio of cyclic carbonate, chain carbonate and chain carboxylic acid ester is (1-15):(20-70):(5-20).
[0022] According to a fourth aspect of the present application, a battery is provided, the battery comprising the electrolyte provided by the third aspect.
[0023] Furthermore, the battery further comprises a negative electrode sheet containing a negative electrode active material; and / or,
[0024] The battery also includes a positive electrode sheet containing a positive electrode active material;
[0025] Preferably, the negative electrode active material includes a carbon-based negative electrode material; the positive electrode active material includes Li2MnO3, LiMn 0.375 Ni 0.375 Co0.25 At least one of O2;
[0026] More preferably, the positive electrode active material is Li2MnO3, LiMn 0.375 Ni 0.375 Co 0.25 O2 mixture, including Li2MnO, LiMn 0.375 Ni 0.375 Co 0.25 The molar ratio of O2 is (0~25):(75~100).
[0027] By applying the technical solution of the present application, an electrolyte functional additive having a specific structural formula is applied as an electrolyte additive to a battery. On the one hand, the electrolyte functional additive can form a uniform and dense protective film (i.e., CEI film) on the surface of the positive electrode, effectively inhibiting the oxidative decomposition of the electrolyte under high voltage, reducing the dissolution of transition metals on the surface of the positive electrode, avoiding the reduction of transition metals on the surface of the negative electrode to destroy the SEI film, reducing interfacial side reactions, and reducing the interfacial impedance of the negative electrode, thereby reducing the internal resistance of the battery; on the other hand, the N-Si bond in the structural formula of the electrolyte functional additive can eliminate harmful substances such as water and HF. Through the reaction of the N-Si bond with these harmful substances, the proton concentration can be effectively reduced to prevent these proton impurities from damaging the SEI film and the CEI film, while improving the chemical stability of the electrolyte, thereby effectively improving the problem of severe capacity decay during the battery cycle at high voltage and extending the cycle life of the battery. DETAILED DESCRIPTION
[0028] As described in the background of this application, the battery in the prior art has the problem of capacity decay during the cycle at high voltage. In order to solve the above problem, the first aspect of this application provides an electrolyte additive composition, including a lithium salt additive and an electrolyte functional additive, and the structural formula of the electrolyte functional additive is shown in Formula 1:
[0029]
[0030] During the battery charging and discharging process, especially the first charging and discharging, the electrolyte functional additives can undergo oxidation reactions on the positive electrode surface to form a thin protective film (i.e., CEI film). The electrolyte functional additives contain specific chemical bonds, such as N-Si bonds. These functional groups have the activity of reacting with the surface of the positive electrode material or the decomposition products of the electrolyte functional additives, and can participate in the formation of the CEI film through chemical bonds during the electrochemical process. For example, the Si element can form a stable compound with the O element or the F element, thereby forming a part of the CEI film. This film can prevent or slow down the subsequent electrolyte decomposition reaction, inhibit side reactions, protect the structural stability of the positive electrode material, and reduce the dissolution of transition metals. In this way, by forming a stable and dense film on the positive electrode surface, the interface impedance of the electrode surface can be reduced, which means that the electron and ion conduction paths inside the battery are smoother, reducing the energy loss of the battery during the charge and discharge cycle.
[0031] Trace amounts of water in the electrolyte can undergo hydrolysis to generate hydrogen and harmful protons (H + ), these protons can further trigger side reactions in the electrolyte and the positive and negative electrode materials, accelerating the battery capacity decay. The chemical bonds in the electrolyte functional additives, such as N-Si bonds, can form stable complexes with the protons in the water molecules, thereby eliminating moisture, reducing the generation of hydrogen and the proton concentration, and improving the stability of the electrolyte. At the same time, it can also form stable chemical bonds with the fluorine atoms in HF, thereby neutralizing HF, reducing its concentration in the electrolyte, and improving the stability of the electrolyte. In this way, by reducing the water and HF in the electrolyte, the chemical stability of the electrolyte can be significantly improved and its decomposition under high voltage can be reduced. In addition, the chemical bonds in the electrolyte functional additives, such as N-Si bonds, can react with the proton impurities (H + ) reaction, which can effectively reduce the proton concentration and reduce the impact of proton concentration on SEI membrane and CEI membrane.
[0032] In summary, electrolyte functional additives can effectively improve the problem of severe capacity decay during battery cycling by improving the chemical properties of the electrolyte and the physicochemical properties of the electrode surface, protecting the battery interface, reducing side reactions, lowering internal resistance, eliminating water and HF in the electrolyte, and improving electrolyte stability. In particular, they can improve the electrolyte's tolerance to high voltage conditions, keep the battery stable within a wider operating voltage range, and enable the battery to operate more effectively at high voltage without rapid capacity decay, thereby extending the battery's cycle life.
[0033] In addition, by introducing functional additives to the electrolyte, the formation of a protective film can be promoted, the loss of active substances and the decline in electrochemical activity can be reduced, and the voltage drop of the battery during the cycle process can be reduced, thereby promoting the improvement of the overall cycle performance of the battery; in addition, by reducing the side reactions of the electrolyte and electrode materials, especially inhibiting the generation of harmful gases, the internal pressure of the battery and the risk of thermal runaway are reduced, thereby improving the safety of the battery.
[0034] In some embodiments, the mass ratio of the lithium salt additive to the electrolyte functional additive is (0.5-1):(0.3-1).
[0035] Lithium salt additives have high oxidation stability and can participate in electrochemical reactions. They can maintain the stability of the electrolyte under high voltage and reduce electrolyte decomposition. At the same time, the chemical bonds in the electrolyte functional additives can eliminate H2O and HF in the electrolyte. Therefore, the synergistic effect of lithium salt additives and electrolyte functional additives can significantly improve the stability of the electrolyte under high voltage conditions.
[0036] The electrolyte functional additive forms a uniform and dense CEI film on the positive electrode surface, reducing the side reactions of the electrolyte on the positive electrode surface and the dissolution of transition metals; at the same time, the lithium salt additive can participate in the formation of SEI film and CEI film. The joint action of the electrolyte functional additive and the lithium salt additive can promote the stability and density of the film, thereby reducing the interface impedance and reducing side reactions. By reducing the side reactions inside the battery, the discharge capacity and average voltage of the battery can be maintained, thereby improving the cycle life of the battery.
[0037] In addition to improving the cycle life, the introduction of lithium salt additives can also improve the performance of the battery at high and low temperatures, reduce the generation of harmful gases inside the battery (such as H2, CO, CO2, etc.), reduce the internal pressure of the battery and the risk of thermal runaway, thereby improving the safety performance of the battery.
[0038] In summary, through the mutual cooperation of lithium salt additives and electrolyte functional additives, we can start from improving electrolyte stability, optimizing the formation of SEI film / CEI film, extending battery cycle life, improving battery performance at high and low temperatures, and improving battery safety. This will enable the battery to maintain more stable performance and longer service life when facing high voltage, and meet the high requirements of modern electronic equipment and new energy vehicles for battery performance.
[0039] The mass ratio of the lithium salt additive to the electrolyte functional additive is (0.5-1): (0.3-1), for example, it can be 0.5:1, 0.8:1, 1:1, 0.5:0.3 or any two of them. By limiting the mass ratio of the lithium salt additive to the electrolyte functional additive, the chemical properties of the electrolyte and the physical structure of the protective film can be optimized to ensure the conductivity, chemical stability and electrochemical window of the electrolyte, improve the performance of the battery at different temperatures, and is particularly suitable for use in environments with large temperature fluctuations, such as outdoor energy storage equipment.
[0040] The present application does not limit the specific type of lithium salt additive, which can be a conventional lithium salt additive in the art. For example, in some preferred embodiments, the lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO2F2), lithium borate, lithium difluoroborate, and lithium hexafluorophosphate.
[0041] In some embodiments, the electrolyte additive composition further includes a carbonate additive; the mass ratio of the carbonate additive to the electrolyte functional additive is (0-1): (0.3-1).
[0042] Carbonate additives can form an SEI film on the surface of the negative electrode. The formation of the SEI film can reduce the formation of lithium dendrites and the direct oxidation of the negative electrode material, thereby reducing the risk of battery short circuit and further improving the cycle life and safety of the battery.
[0043] Carbonate additives have high oxidation potential, good chemical stability and thermal stability. By adding carbonate additives, the conductivity of the electrolyte can be improved, and the electrochemical window of the electrolyte can be further broadened, so that the electrolyte remains stable in a wider voltage range, which helps the battery maintain performance when operating at high voltage. Secondly, the addition of carbonate solvents can optimize the volatility of the electrolyte, reduce the volatilization of the electrolyte at high temperature or during charging and discharging, and enhance the thermal stability of the battery. It is especially suitable for equipment that requires high power output and improves the overall safety of the battery. In addition, carbonate additives have a low freezing point, which can improve the fluidity and conductivity of the electrolyte under low temperature conditions, thereby improving the performance and reliability of the battery in low temperature environments.
[0044] In summary, by introducing carbonate additives, the composition of the electrolyte is optimized under the joint action of lithium salt additives, electrolyte functional additives and carbonate additives. In addition to further improving the cycle stability and voltage drop of the battery at high voltage, it can also significantly improve the safety and low-temperature performance of the battery.
[0045] The mass ratio of carbonate additives to electrolyte functional additives is (0-1): (0.3-1), for example, it can be 0.1:1, 0.5:1, 1:1, 1:0.5, 1:0.3 or any two of them. By limiting the ratio of carbonate additives to electrolyte functional additives, the physical and chemical properties of the entire electrolyte can be optimized, including viscosity, conductivity and chemical stability, thereby improving the overall performance of the battery.
[0046] The present application does not limit the specific type of carbonate additives, and the carbonate additives may be conventional carbonate additives in the art. For example, in some embodiments, the carbonate additives include at least one of vinylene carbonate (VC) and fluoroethylene carbonate.
[0047] In some embodiments, the electrolyte additive composition further includes a sulfur-containing additive; the mass ratio of the sulfur-containing additive to the electrolyte functional additive is (0.5-3): (0.3-1).
[0048] Sulfur-containing additives can promote the formation of SEI and CEI films, optimize the physical properties of SEI / CEI films, and further reduce the interfacial impedance of the battery. Sulfur-containing additives have good thermal and electrochemical stability, which can not only improve the stability and hydrolysis resistance of the electrolyte at high voltage, but also maintain the integrity of the SEI / CEI film at higher temperatures, reduce the negative impact of high-temperature charge and discharge cycles on battery performance, and enable the battery to maintain good performance in high-temperature environments. Sulfur-containing additives usually have good solvent compatibility and conductivity, which can improve the overall conductivity of the electrolyte and optimize the charge and discharge efficiency of the battery.
[0049] In summary, the addition of sulfur-containing additives can not only further reduce the capacity decay and voltage drop of the battery during the cycle, but also enhance the stability of the electrolyte and the high-temperature performance of the battery, optimize the conductivity, enhance the interface stability of the battery, and further improve the overall performance of the battery.
[0050] The mass ratio of the sulfur-containing additive to the electrolyte functional additive is (0.5-3): (0.3-1), for example, it can be 0.5:1, 0.8:1, 1:1, 2:1, 3:1, 3:0.5, 3:0.3 or any two of them. By limiting the mass ratio of the sulfur-containing additive to the electrolyte functional additive within the above range, the SEI / CEI film formation inside the battery can be optimized through synergistic effects, which can further reduce the capacity decay and voltage drop of the battery during the cycle process, and can also improve the thermal stability and low temperature performance of the battery.
[0051] The present application does not limit the specific type of sulfur-containing additive, and it can be a conventional sulfur-containing additive in the art. For example, in some embodiments, the sulfur-containing additive includes at least one of propylene sulfite (PS), 1,3-propane sultone (PST), and ethylene sulfate (DTD).
[0052] In a third aspect of the present application, an electrolyte is provided, the electrolyte comprising a lithium salt, an organic solvent and the electrolyte additive composition provided in the second aspect.
[0053] Due to the inclusion of the above-mentioned electrolyte additive composition, the electrolyte can form a more stable electrochemical environment inside the battery, effectively improve the problems of severe capacity decay and voltage drop during the battery cycle at high voltage, and extend the cycle life of the battery. The electrolyte is suitable for lithium-ion batteries.
[0054] Lithium salt is the main source of conductive ions in the electrolyte. In some embodiments, the mass fraction of lithium salt in the electrolyte is 10% to 15%. By limiting the amount of lithium salt added within the above range, it is possible to ensure that the electrolyte has sufficient conductivity, ensure efficient ion transmission during the charge and discharge process of the battery, and at the same time, ensure that there is enough lithium salt to participate in the formation of the SEI / CEI film.
[0055] The mass fraction of the lithium salt in the electrolyte is 10% to 15%, for example, 10%, 11%, 12%, 13%, 14%, 15% or a range consisting of any two thereof.
[0056] In some embodiments, the mass fraction of the electrolyte additive composition in the electrolyte is greater than 0 and less than or equal to 5%. By limiting the addition amount of the electrolyte additive composition to the above range, it is ensured that the electrolyte additive composition can play an effective role in the electrolyte to the maximum extent.
[0057] The mass fraction of the electrolyte additive composition in the electrolyte is greater than 0 and less than or equal to 5%, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5% or a range consisting of any two thereof.
[0058] Organic solvent is the main component of the electrolyte and is responsible for transporting lithium ions. In some embodiments, the mass fraction of organic solvent in the electrolyte is 80% to 90%. By limiting the amount of organic solvent added within the above range, sufficient fluidity can be provided to ensure the rapid transmission of lithium ions between electrodes, thereby maintaining the high conductivity of the battery; secondly, the appropriate solvent ratio is conducive to the formation of a stable and dense interface film, promotes the formation of SEI / CEI film, and reduces side reactions; in addition, it also helps to ensure that the electrolyte has suitable viscosity, conductivity and chemical stability, and can maintain stable lithium ion transmission even under low or high temperature conditions, thereby improving the charging and discharging efficiency, stability and safety of lithium-ion batteries.
[0059] The mass fraction of the organic solvent in the electrolyte is 80% to 90%, for example, 80%, 82%, 84%, 86%, 88%, 90% or a range consisting of any two thereof.
[0060] Through the synergistic effect of lithium salt, electrolyte additive composition and organic solvent, the viscosity and conductivity of the electrolyte can be optimized to maintain good stability, thereby improving the charge and discharge performance and energy efficiency of the battery in high and low temperature environments.
[0061] This application does not limit the proportion of each additive in the electrolyte, as long as the above requirements are met. For example, in some embodiments, the mass fraction of the electrolyte functional additive in the electrolyte is 0.3% to 1%. By limiting the amount of electrolyte functional additives added, it can not only play its role in improving severe capacity decay and voltage drop, but also avoid changes in electrolyte viscosity or increased costs, which is helpful to achieve electrolyte formulation optimization and lithium-ion battery performance improvement.
[0062] In some embodiments, the mass fraction of the electrolyte functional additive in the electrolyte is 0.3% to 1%, such as 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any two of them. By limiting the amount of electrolyte functional additive added, the role of the electrolyte functional additive can be maximized, effectively improving the capacity retention rate and reducing the voltage drop when the battery is cycled under high voltage, and achieving electrolyte formulation optimization and battery electrochemical performance improvement.
[0063] In some embodiments, the mass fraction of the lithium salt additive in the electrolyte is 0.5% to 1%, such as 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any two thereof. The lithium salt additive can participate in the electrochemical reaction. By limiting the amount of the lithium salt additive, in addition to maintaining the stable output of the battery under high voltage cycling and effectively reducing the voltage drop, the energy density of the battery can also be improved.
[0064] In some embodiments, the mass fraction of carbonate additives in the electrolyte is 0-1%, such as 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any two of them. By limiting the amount of carbonate additives added, the formation of a uniform and dense SEI film can be promoted to maximize its multiple functions.
[0065] In some embodiments, the mass fraction of the sulfur-containing additive in the electrolyte is 0.5% to 3%, such as 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, or any two thereof. By limiting the amount of sulfur-containing additive added, the effectiveness of the additive can be ensured while taking into account the cost.
[0066] The present application does not limit the specific type of organic solvent, which can be a conventional organic solvent in the art. In some embodiments, the organic solvent includes at least one of cyclic carbonates, chain carbonates, and chain carboxylates. In some preferred embodiments, the organic solvent includes cyclic carbonates, chain carbonates, and chain carboxylates, which can combine the advantages of carbonates, chain carbonates, and chain carboxylates to improve the overall performance of the battery. Specifically, cyclic carbonates can still maintain good conductivity at low temperatures, which can promote the formation of a stable SEI film at low temperatures, while chain carbonates and chain carboxylates help to reduce viscosity and have better stability at high temperatures. In this way, by limiting the specific type of organic solvent, the stability of the electrolyte at high and low temperatures can be improved, and the capacity retention rate of the battery during high and low temperature cycles can be improved to meet the needs of the battery in different application scenarios.
[0067] When the organic solvent includes cyclic carbonate, chain carbonate and chain carboxylic acid ester, the mass ratio of cyclic carbonate, chain carbonate and chain carboxylic acid ester is (1-15):(20-70):(5-20). By limiting the ratio of cyclic carbonate, chain carbonate and chain carboxylic acid ester, the electrolyte formulation can be optimized, taking into account the balance of lithium ion transmission rate, SEI / CEI film formation, high and low temperature performance, cost-effectiveness, internal resistance reduction, chemical stability and battery safety.
[0068] The present application does not limit the specific preparation method of the electrolyte, as long as it contains the above components. For example, the specific preparation method of the electrolyte includes the following steps: adding the electrolyte additive composition to the organic solvent under a protective atmosphere, then adding the lithium salt, stirring and mixing at a first temperature to obtain the electrolyte; wherein the protective atmosphere can be argon gas, and the first temperature can be 5 to 15°C.
[0069] A fourth aspect of the present application provides a battery, comprising the electrolyte provided in the third aspect.
[0070] Due to the inclusion of the above-mentioned electrolyte, the battery has excellent cycle stability, especially high capacity retention and low voltage drop when cycled under high voltage conditions. In addition, the battery can meet the needs of different temperature scenarios.
[0071] In some embodiments, the battery further includes a negative electrode sheet containing a negative electrode active material and a positive electrode sheet containing a positive electrode active material.
[0072] The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer formed of a negative electrode active material and disposed on the surface of the negative electrode current collector.
[0073] When preparing the negative electrode sheet, the negative electrode active material, the first conductive agent, and the first binder can be dispersed in an appropriate amount of solvent, and fully stirred and mixed to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and cutting. In a specific embodiment, the negative electrode active layer includes 70% to 99% of graphite negative electrode material, 0.5% to 15% of conductive agent, and 0.5% to 15% of binder in terms of mass percentage.
[0074] Among them, the material of the negative electrode current collector can be at least one of copper foil, nickel foam, and copper foam; the first conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene; the first binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyvinyl alcohol, and sodium polyacrylate.
[0075] The present application does not limit the specific type of the negative electrode active material in the negative electrode sheet, and it can be a negative electrode active material commonly used in current batteries, such as at least one of graphite, hard carbon, soft carbon, mesophase carbon microspheres, and silicon-based negative electrode materials. In some preferred embodiments, the negative electrode active material includes a carbon-based negative electrode material.
[0076] The positive electrode sheet includes a positive electrode collector and a positive electrode active layer formed of a positive electrode active material and disposed on the surface of the positive electrode collector.
[0077] When preparing the positive electrode sheet, the positive electrode active material, the second conductive agent, and the second binder can be dispersed in an appropriate amount of solvent, and fully stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector, and the positive electrode sheet is obtained after drying, rolling and slitting. In a specific embodiment, the positive electrode active layer includes 70% to 99% of the positive electrode active material, 0.5% to 15% of the conductive agent, and 0.5% to 15% of the binder in terms of mass percentage.
[0078] Among them, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil; the second conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the second binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polyethylene, polypropylene, polyvinyl alcohol, and sodium polyacrylate.
[0079] The present application does not limit the specific type of positive electrode active material in the positive electrode sheet, which can be a positive electrode active material commonly used in current batteries, such as at least one composite oxide of lithium and metals such as cobalt, nickel, manganese and their combinations. Specifically, it can be at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, lithium iron phosphate, lithium nickel manganese oxide, and lithium-rich manganese-based materials. In some preferred embodiments, the positive electrode active material is Li2MnO3, LiMn 0.375 Ni 0.375 Co 0.25 O2 mixture, including Li2MnO3, LiMn 0.375 Ni 0.375 Co 0.25 The molar ratio of O2 is (0~25):(75~100).
[0080] The battery also includes a diaphragm. The present application does not limit the specific selection of the diaphragm material, and it can be a diaphragm material commonly used in batteries, such as a polypropylene diaphragm, a polyethylene diaphragm, a polypropylene / polyethylene double-layer composite diaphragm, a polypropylene / polyethylene / polypropylene (PP / PE / PP) three-layer composite diaphragm, etc.
[0081] When preparing the battery, the positive electrode sheet, the separator and the negative electrode sheet are wound or stacked to obtain the battery cell, and the battery cell is encapsulated in a pre-stamped aluminum-plastic film. After the encapsulated battery is dried to remove moisture, the electrolyte is injected into the dry battery. After the battery is aged, formed and sealed for the second time, the battery preparation is completed.
[0082] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0083] Example 1
[0084] The electrolyte of this embodiment is composed of an organic solvent, a lithium salt and an additive; the additive includes vinylene carbonate, lithium difluorophosphate, 1,3-propane sultone and a functional additive as shown in Formula 1, and the CAS number is 3442-82-8;
[0085] Among them, the mass fraction of vinylene carbonate in the electrolyte is 0.5%, the mass fraction of lithium difluorophosphate in the electrolyte is 0.5%, the mass fraction of 1,3-propane sultone in the electrolyte is 2%, and the mass fraction of functional additives in the electrolyte is 0.5%;
[0086]
[0087] The lithium salt is lithium hexafluorophosphate, and its mass fraction in the electrolyte is 15%; the mass fraction of the organic solvent in the electrolyte is 81.5%, and it is composed of fluoroethylene carbonate, ethylene carbonate, ethyl difluoroacetate, and diethyl carbonate. Based on the total mass of the organic solvent being 100%, the mass fraction of fluoroethylene carbonate is 10%, the mass fraction of ethylene carbonate is 10%, the mass fraction of ethyl difluoroacetate is 15%, and the mass fraction of diethyl carbonate is 65%.
[0088] The preparation method of the electrolyte of this embodiment includes: under an argon atmosphere, according to the above mass fractions, adding a formula amount of vinylene carbonate, lithium difluorophosphate, 1,3-propane sultone and functional additives to an organic solvent, then adding lithium hexafluorophosphate, stirring and mixing at a temperature of 10° C. to obtain the electrolyte.
[0089] Example 2
[0090] The difference from Example 1 is that the mass fraction of vinylene carbonate in the electrolyte is 0.2%, and the mass fraction of the organic solvent is 81.8%.
[0091] Example 3
[0092] The difference from Example 1 is that the mass fraction of vinylene carbonate in the electrolyte is 0.8%, and the mass fraction of the organic solvent is 81.2%.
[0093] Example 4
[0094] The difference from Example 1 is that the mass fraction of lithium difluorophosphate in the electrolyte is 0.2%, and the mass fraction of the organic solvent is 81.8%.
[0095] Example 5
[0096] The difference from Example 1 is that the mass fraction of lithium difluorophosphate in the electrolyte is 0.8%, and the mass fraction of the organic solvent is 81.2%.
[0097] Example 6
[0098] The difference from Example 1 is that the mass fraction of 1,3-propane sultone in the electrolyte is 0.5%, and the mass fraction of the organic solvent is 83%.
[0099] Example 7
[0100] The difference from Example 1 is that the mass fraction of 1,3-propane sultone in the electrolyte is 3%, and the mass fraction of the organic solvent is 80.5%.
[0101] Example 8
[0102] The difference from Example 1 is that the mass fraction of the functional additive in the electrolyte is 0.2%, and the mass fraction of the organic solvent is 81.8%.
[0103] Example 9
[0104] The difference from Example 1 is that the mass fraction of the functional additive in the electrolyte is 0.8%, and the mass fraction of the organic solvent is 81.2%.
[0105] Example 10
[0106] The difference from Example 1 is that the mass fraction of the functional additive in the electrolyte is 1%, and the mass fraction of the organic solvent is 81%.
[0107] Embodiment 11
[0108] The difference from Example 1 is that the mass fraction of the functional additive in the electrolyte is 1.5%, and the mass fraction of the organic solvent is 80.5%.
[0109] Example 12
[0110] The difference from Example 1 is that vinylene carbonate, lithium difluorophosphate and 1,3-propane sultone are not added, and the mass fraction of the organic solvent is 84.5%.
[0111] Example 13
[0112] The difference from Example 1 is that lithium difluorophosphate and 1,3-propane sultone are not added, and the mass fraction of the organic solvent is 84%.
[0113] Embodiment 14
[0114] The difference from Example 1 is that vinylene carbonate and 1,3-propane sultone are not added, and the mass fraction of the organic solvent is 84%.
[0115] Embodiment 15
[0116] The difference from Example 1 is that vinylene carbonate and lithium difluorophosphate are not added, and the mass fraction of the organic solvent is 82.5%.
[0117] Comparative Example 1
[0118] The difference from Example 1 is that no functional additive is added and the mass fraction of the organic solvent is 82%.
[0119] Comparative Example 2
[0120] The difference from Example 1 is that the functional additive is replaced by an additive as shown in Formula 2:
[0121]
[0122] Comparative Example 3
[0123] The difference from Example 1 is that the functional additive is replaced by an additive as shown in Formula 3:
[0124]
[0125] Test example
[0126] The electrolytes of the embodiment and the comparative example were applied to lithium-ion batteries, and the performance of the lithium-ion batteries was tested. The specific preparation method of the lithium-ion battery includes: mixing graphite, acetylene black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 94:1:2:3 to form a negative electrode slurry; coating the negative electrode slurry on a copper foil current collector, vacuum drying, and preparing a negative electrode sheet;
[0127] The positive electrode material (0.25Li2MnO3 · 0.75LiMn 0.375 Ni 0.375 Co 0.25 O2), acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 94:3:3 to form a positive electrode slurry; the positive electrode slurry is coated on an aluminum foil current collector, and vacuum dried to obtain a positive electrode sheet;
[0128] The positive electrode sheet, Celgard2400 separator and negative electrode sheet are wound or stacked to obtain a battery cell, and the battery cell is encapsulated in a pre-stamped aluminum-plastic film. After the encapsulated battery is dried to remove moisture, the electrolyte of the embodiment and the comparative example is injected into the dried battery. After the battery is aged, formed and sealed for a second time, a lithium ion battery is obtained.
[0129] The following electrochemical tests were performed using a Xinwei charge and discharge test cabinet.
[0130] (1) Normal temperature cycle performance test:
[0131] At 25°C, the lithium-ion battery is charged at a constant current of 0.5C (nominal capacity) to a voltage of 4.6V, then charged at a constant voltage of 4.6V to a current ≤ 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The lithium-ion battery is charged and discharged 1000 times under the above conditions.
[0132] Capacity retention rate (%) of a lithium-ion battery after 1000 cycles = (discharge capacity at the 1000th cycle / initial discharge capacity) × 100%.
[0133] The average voltage (V) of a lithium-ion battery after 1000 cycles = discharge energy at the 1000th cycle / discharge capacity at the 1000th cycle.
[0134] (2) High temperature cycle performance test
[0135] At 45°C, the lithium-ion battery was charged at a constant current of 1.0C (nominal capacity) to a voltage of 4.6V, then charged at a constant voltage of 4.6V to a current of ≤0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The lithium-ion battery was charged and discharged 800 times under the above conditions.
[0136] Capacity retention rate (%) of the lithium-ion battery after 800 cycles = (discharge capacity at the 800th cycle / initial discharge capacity) × 100%.
[0137] The average voltage (V) of the lithium-ion battery after 800 cycles = the discharge energy at the 800th cycle / the discharge capacity at the 800th cycle.
[0138] The test results are shown in Table 1.
[0139] Table 1
[0140]
[0141] By comparing Examples 1 to 15 with Comparative Example 1, it can be seen that by introducing a functional additive having the structure shown in Formula 1, the capacity retention rate of 1000 cycles at room temperature and 800 cycles at high temperature can be significantly improved and the voltage drop can be reduced, thereby solving the problem of rapid capacity decay and voltage decay in high-voltage material system batteries.
[0142] Comparing Examples 1 to 15 with Comparative Examples 2 and 3, it can be seen that although the functional additives of Comparative Example 2 also contain N-Si bonds, and the functional additives of Comparative Example 3 contain C=O bonds and cyclic structures, the improvement of the cycle performance and voltage drop is limited. Specifically, the capacity retention rate and the degree of voltage drop reduction of Examples 1 to 7 and Example 9 after 1000 cycles at room temperature and 800 cycles at high temperature are greater than those of Comparative Example 2, and the capacity retention rate and the degree of voltage drop reduction of Example 8 after 1000 cycles at room temperature and 800 cycles at high temperature are much greater than those of Comparative Example 2. However, due to the low addition amount of the functional additives of Example 8, the capacity retention rate and the degree of voltage drop reduction of Example 8 after 800 cycles at high temperature are not as good as those of Comparative Example 2. The capacity retention rate and the degree of voltage drop reduction of Examples 1 to 15 after 1000 cycles at room temperature and 800 cycles at high temperature are greater than those of Comparative Example 3. It can be seen that the functional additive with the structure shown in Formula 1 in the present application is not the independent effect of a single functional group, but the entire structure produces multiple synergistic effects in the electrolyte, and this synergistic effect is the key to improving battery performance and stability.
[0143] By comparing Examples 1 to 15, it can be seen that Example 4 does not meet the mass ratio of lithium salt additive to electrolyte functional additive of (0.5-1): (0.3-1), Example 8 has a low amount of functional additives, and Example 11 has a high amount of functional additives, so the improvement is not as good as Examples 1 to 3, 5 to 7 and Example 10. By limiting the mass fraction of each component within a specific range, the cycle capacity retention rate of the battery at high voltage can be further improved and the voltage drop can be reduced.
[0144] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. An electrolyte additive composition, characterized in that: The electrolyte additive composition comprises a lithium salt additive and an electrolyte functional additive, and the structural formula of the electrolyte functional additive is shown in Formula 1:
2. The electrolyte additive composition according to claim 1, characterized in that: The mass ratio of the lithium salt additive to the electrolyte functional additive is (0.5-1): (0.3~1)。 3. The electrolyte additive composition according to claim 2, characterized in that: The electrolyte additive composition further includes a carbonate additive; the mass ratio of the carbonate additive to the electrolyte functional additive is (0.1-1): (0.3-1); Preferably, the carbonate additive includes at least one of vinylene carbonate and fluoroethylene carbonate; Preferably, the lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium borate, lithium difluoroborate, and lithium hexafluorophosphate.
4. The electrolyte additive composition according to claim 2 or 3, characterized in that: The electrolyte additive composition further includes a sulfur-containing additive; the mass ratio of the sulfur-containing additive to the electrolyte functional additive is (0.5-3): (0.3-1); Preferably, the sulfur-containing additive includes at least one of propylene sulfite, 1,3-propane sultone, and ethylene sulfate.
5. An electrolyte, characterized in that: The electrolyte comprises a lithium salt, an organic solvent and the electrolyte additive composition according to any one of claims 1 to 4.
6. The electrolyte according to claim 5, characterized in that The mass fraction of the lithium salt in the electrolyte is 10% to 15%; and / or, The mass fraction of the organic solvent in the electrolyte is 80% to 90%; and / or, The mass fraction of the electrolyte additive composition in the electrolyte is greater than 0 and less than or equal to 5%.
7. The electrolyte according to claim 5 or 6, characterized in that The mass fraction of the electrolyte functional additive in the electrolyte is 0.3% to 1%; and / or, The mass fraction of the lithium salt additive in the electrolyte is 0.5% to 1%; and / or, The mass fraction of the carbonate additive in the electrolyte is 0.1-1%; and / or, The mass fraction of the sulfur-containing additive in the electrolyte is 0.5% to 3%.
8. The electrolyte according to claim 5 or 6, characterized in that The organic solvent includes at least one of cyclic carbonate, chain carbonate, and chain carboxylic acid ester; Preferably, the organic solvent comprises cyclic carbonate, chain carbonate and chain carboxylic acid ester, wherein the mass ratio of the cyclic carbonate, the chain carbonate and the chain carboxylic acid ester is (1-15):(20-70):(5-20).
9. A battery, characterized in that: The battery comprises the electrolyte according to any one of claims 5 to 8.
10. The battery according to claim 9, characterized in that The battery further comprises a negative electrode sheet containing a negative electrode active material; and / or, The battery also includes a positive electrode sheet containing a positive electrode active material; Preferably, the negative electrode active material includes a carbon-based negative electrode material; the positive electrode active material includes Li2MnO3, LiMn 0.375 Ni 0.375 Co 0.25 At least one of O2; More preferably, the positive electrode active material is Li2MnO3, LiMn 0.375 Ni 0.375 Co 0.25 O2 mixture, including Li2MnO3, LiMn 0.375 Ni 0.375 Co 0.25 The molar ratio of O2 is (0~25):(75~100).
Citation Information
Patent Citations
Electrolyte composition and its use in lithium-ion batteries
CA2960489A1
Silane functionalized ionic liquids
CN108701866A
Lithium ion battery electrolyte and lithium ion battery
CN113394457A
Non-aqueous electrolyte and lithium ion battery
CN115966766A
Nonaqueous electrolyte and nonaqueous electrolyte battery including the same
JP2013232298A